Małgorzata Szumowska – a Few Scenes from a Filmmaker’s Life (2000-2008) - Pławuszewski, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
Małgorzata Szumowska – her strong position during the last decade in the history of Polish cinema seems unquestionable. Speaking with her own, original voice, she has successfully refused to be pigeonholed. The only thing one can be sure of in reference to Małgorzata Szumowska is that she will keep moving forward artistically. The main goal of the article is to examine this interesting journey, following selected threads, in particular, the need for love and facing death or a serious illness, in Szumowska’s filmography over the last decade.